The Growth of the Church through Mission Great Commission, Matthew 28:19-20 - Tony Tedjo; Rita Oktavia Gunarto; Cindy Clarrisa Gabriela Febrian; Agus Setiawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Great Commission, which reads to make disciples of all nations, cannot be separated from its impact on the growth of the church in terms of quantity and quality. The results of the mission that are growth as increased the number and faith of believers. However, the church is too busy with programs which seem just only an euphoria of its activities, without a focus on the growth impact of the church and congregation. The church often isolates itself by high walls building as like “member only”, so that the gospel is not communicated and is not properly nurtured in the wider community. That’s why God's church being underdeveloped. To describe a biblical study of mission and discipleship in the Great Commission and its implications for church growth, so then researchers use research methods from literature and related journals to find the meaning of church growth by God's great Commission.